Self-incompatibility in Papaver: advances in integrating the signalling network. (20th March 2014) - Eaves, Deborah J.; Flores-Ortiz, Carlos; Haque, Tamanna; Lin, Zongcheng; Teng, Nianjun; Franklin-Tong, Vernonica E.
Abstract : Self-fertilization, which results in reduced fitness of offspring, is a common problem in hermaphrodite angiosperms. To prevent this, many plants utilize SI (self-incompatibility), which is determined by the multi-allelic S -locus, that allows discrimination between self (incompatible) and non-self (compatible) pollen by the pistil. In poppy ( Papaver rhoeas ), the pistil S- determinant ( PrsS ) is a small secreted protein which interacts with the pollen S -determinant PrpS, a 20 kDa novel transmembrane protein. Interaction of matching pollen and pistil S -determinants results in self-recognition, initiating a Ca 2+ -dependent signalling network in incompatible pollen. This triggers several downstream events, including alterations to the cytoskeleton, phosphorylation of sPPases (soluble inorganic pyrophosphatases) and an MAPK (mitogen-activated protein kinase), increases in ROS (reactive oxygen species) and nitric oxide (NO), and activation of several caspase-like activities. This results in the inhibition of pollen tube growth, prevention of self-fertilization and ultimately PCD (programmed cell death) in incompatible pollen. The present review focuses on our current understanding of the integration of these signals with their targets in the SI/PCD network. We also discuss our recent functional expression of PrpS in Arabidopsis thaliana pollen.